DAMPAK MEDIA AUDIO VISUAL PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN TERHADAP HASIL BELAJAR KELAS III SD - Rahmat, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is whether there is an impact and how big an impact audio visual media on civic education learning learning learner outcomes against class III primary school South Pontianak Mujahideen. This research aims to analyze whether there are effects and analyze how much impact audio visual media on learning,citizenship education towards the learning results of learners. This research uses experimental methods with Pre-Experimental Design types of non equivalent control group design. The population of the entire learners from five classes amounted to 167people, as for sampelnya are all learners of 167 people. Data collection technique ismeasurement, data collectin tool was written objective-shaped test. Based on the analysis of data obtained average results post-test experiment class = 79.32 and the results of the average post-test control class = 66.73. This indicates an increase in the results of the learning learners in learning to use the audio visual media. After a test of t obtained thitung 6.88 for dk 62 and ? = 5% is acquired ttabel is 1.6705, which means thitung ? ttabel, then the Ha received, which means there is a significant impact on the use of audiovisual media. From the results of the calculation of effect size (? ?), obtained ? ? of 1.24 high criteria. Means the use of audio visual media on learning Kewarganegaran Education delivers high impact results learning learners. Keywords : Audiovisual Media, The Results Of The Study, Civic Education